1975
DOI: 10.1111/j.1365-2133.1975.tb02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization and differentiation of membrane-bound ATP utilizing enzymes including adenyl cyclase in normal and psoriatic epidermis*

Abstract: The total membrane-bound ATP hydrolytic activity in human epidermis is due to the activities of at least three differently located enzymes, namely Mg++-activated ATPase, phosphomonoesterase and adenyl cyclase. Cytochemical studies on psoriatic epidermis with various inhibitory and stimulatory substances showed reduced activities of ATPase and phosphomonoesterase, and a lack of sensitivity of adenyl cyclase to specific stimulators such as isoproterenol and glucagon. Since no differences of basal adenyl cyclase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…''Adenosine increased cAMP levels in lesioned and uninvolved areas of epidermis obtained from psoriasis patients'' (Duell, 1980). A defective purine nucleotide synthetic pathway has been described in psoriasis patients (Kiehl and Ionescu, 1992) and nucleotide metabolism is altered in psoriatic keratinocytes (Mahrle and Orfanos, 1975). The ability to incorporate [H 3 ]adenine into ATP and adenyl cyclase activity was significantly lower in psoriasis plaques than in uninvolved skin and lower than in normal skin of control subjects (Mui et al, 1975).…”
Section: Skin Pathology Psoriasismentioning
confidence: 98%
“…''Adenosine increased cAMP levels in lesioned and uninvolved areas of epidermis obtained from psoriasis patients'' (Duell, 1980). A defective purine nucleotide synthetic pathway has been described in psoriasis patients (Kiehl and Ionescu, 1992) and nucleotide metabolism is altered in psoriatic keratinocytes (Mahrle and Orfanos, 1975). The ability to incorporate [H 3 ]adenine into ATP and adenyl cyclase activity was significantly lower in psoriasis plaques than in uninvolved skin and lower than in normal skin of control subjects (Mui et al, 1975).…”
Section: Skin Pathology Psoriasismentioning
confidence: 98%
“…Alterations in the cyclic nucleotide system (Voorhees et al, 1974)3 in membrane-bound ATPase and phosphomonoesterase activities (Mahrle & Orfanos, 1975)3 in membrane-associated hydrolases (Mier & Van den Hurk, 1976), in several lipid components such as cholesterol and phospholipids (Gara et al, 1964;Tsambaos & Mahrle, 1979)) and in uptake of labelled sugars into cell membrane (Roelfzema et al, 1981), strongly suggest that aberrations of membranemediated growth control mechanisms may be relevant to the expression of psoriasis (Mahrle & Orfanos, 1977). In a previous communication (Kumar et al, 1983), we reported that psoriatic patients exhibit decreased phosphorylation of red cell membrane polypeptides suggesting that membrane alterations may be part of a basic defect in psoriasis that may involve tissues other than skin.…”
Section: Discussionmentioning
confidence: 99%
“…Functional abnormalities of membrane-bound enzymes in psoriasis are not limited to the disturbance of adenyl cyclase (Wright et al, 1973) but include a decrease of ATPase and acid phosphoesterase activities (Mahrle & Orfanos, 1974;Mahrle& Orfanos, 1975).…”
Section: Abnormal Growth Control Mechanism Can Be Due To Plasma Membrmentioning
confidence: 99%